Exploring Foresight: Addressing Grand Challenges and Shape the Future with Robust Methodologies and Frameworks - Queiroz, Maciel Manuel (2024)
Foresight is the systematic exploration of possible futures to inform present-day decisions. It involves horizon scanning, scenario planning, and vision to anticipate trends and disruptions. Foresight empowers policymakers to navigate uncertainty and design resilient strategies